Meta Analisis Pengaruuh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Hasil Belajar Fisika SMA/MA Peserta Didik - Tiara Alwafa Nissa Huang; Wahyuni Satria Dewi; Gusnedi Gusnedi; Putri Dwi Sundari (Jurnal Penelitian Pendidikan IPA, 2023)
Various efforts have been made to realize ideal physics learning, one of which is by applying the right learning model. This study's objective was to ascertain the impact of cooperative model type think pair share on students' physics learning outcomes based on instructional materials and media. This study collected 17 articles from national and international journals to be discussed using the meta-analysis method. Articles used in this study have been analyzed and meet the categories for effect size calculation and are grouped based on two indicators, namely based on subject matter and learning media. The results showed that the think pair share learning approach had an overall positive effect of 1.98 on students' learning outcomes in physics, with a high influence category. According to the learning materials, the material with a magnitude and measurement of 5.03 and a high influence category is where the think pair share model has the most impact. Based on learning media, the most effective influence on animation media is 1.61 with a high influence category. The TPS learning model is most effective in improving the physics learning outcomes of students on the material of quantities and measurements. The most effective learning tool for enhancing students' physics learning outcomes when using the TPS model is animated learning material